OBESITAS SENTRAL PADA ORANG DEWASA: STUDI KOHOR PROSPEKTIF DI KOTA BOGOR - Sudikno Sudikno; Woro Riyadina; Ekowati Rahajeng (GIZI INDONESIA, 2018)
Central obesity is one of the public health problems in developing countries. This study aims to analyze the dynamic risk factors for central obesity in adults. This study used secondary data "Cohort Study of Non-Communicable Diseases Risk Factors" observing period for six years. The study design was a prospective cohort. The subjects were all household members aged 25 years and above with the criteria remaining in the study area, healthy, non-physically disabled, non-pregnant, having normal abdominal circumference (male ≤ 90 cm and female ≤80 cm) on baseline study, not suffering from non-communicable diseases (hypertension, diabetes mellitus, cancer, stroke, chronic obstructive pulmonary disease) at the baseline of the study, and completeness of the data. The number of subjects at the baseline of the study were 1510, consisting of 613 men and 897 women. The results showed that a cumulative incidence of central obesity during the 6-year observation period of 837 (55.4%). Multivariate cox regression analysis showed that the risk factors for central obesity in adults were gender, age group, marital status, and physical activity. This study concluded that female subjects with physical inactivity had more central obesity compared to male subjects with physical inactivity.